Recent Stressful Experiences and Electronic Nicotine Product Use Among Young Adults - Gherghe, Anda; Fahey, Kalina M.L.; Cservenka, Anita (Current Psychiatry Research and Reviews, 2025)
Background and ObjectiveThe goal of the current study was to examine how specific recent stressors are related to electronic nicotine product use among young adults. Despite increases in electronic nicotine product use among adults, stressors shaping the use of these products remain largely unknown. The current study examined the types and average severity of stressors endorsed between young adults with past 30-day electronic nicotine product use and young adults with no lifetime use, as well as the association between frequency of recent electronic nicotine product use and average severity of stressors.Methods175 current electronic nicotine product users and 333 lifetime abstainers of electronic nicotine products and cigarettes reported recent stressful experiences that occurred in the past six months, as well as lifetime and past 30-day substance use. Chi-square, independent samples t-test, and regression analyses were performed.ResultsThere were no significant group differences in the primary type of stressor experienced (p = 0.320) or average stress of the three recent stressful experiences reported (p = 0.246). There was no significant relationship between electronic nicotine product use and average stress of the three recent stressful experiences, controlling for demographic and substance use covariates (p = 0.150). Both current electronic nicotine product users and lifetime abstainers endorsed school, family, and romantic relationship stressors most frequently as their top stressors.ConclusionTo our knowledge, this is the first study to examine group differences in specific stressor categories and perceived stress between current electronic nicotine product users and lifetime abstainers of these products. Given the novel assessment of stressor types, the current study provides a critical starting point for research on this timely topic. In addition, due to the high overlap between stress and nicotine use, future studies should investigate different populations of electronic nicotine product users and other methods to assess stressful experiences.
Keywords: young adults